If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(6-x)-2(3-x)-5=(5-2x)
We move all terms to the left:
4(6-x)-2(3-x)-5-((5-2x))=0
We add all the numbers together, and all the variables
4(-1x+6)-2(-1x+3)-((-2x+5))-5=0
We multiply parentheses
-4x+2x-((-2x+5))+24-6-5=0
We calculate terms in parentheses: -((-2x+5)), so:We add all the numbers together, and all the variables
(-2x+5)
We get rid of parentheses
-2x+5
Back to the equation:
-(-2x+5)
-2x-(-2x+5)+13=0
We get rid of parentheses
-2x+2x-5+13=0
We add all the numbers together, and all the variables
8!=0
There is no solution for this equation
| 3(r-1)=4(6) | | (+9x^2+3x+3x+1)(+9x^2+3x+3x+1)=16 | | 4/7x3=12/21= | | 1.4-0.6=0.2(5+3z) | | (3x+1)(3x+1)(3x+1)(3x+1)=16 | | 4-b÷2=10 | | 60=1/4g+12;g=12 | | 2c=-13 | | 5=15+x | | 20-2t=1/2t+28;t=-3.2 | | 11=2/3x-1;x=15 | | 4x-6,x=5 | | 100−3x=-50 | | 6x2-40=110 | | 650=x+0,25x | | -23=x-8 | | -3(v-3)=-5v+13 | | -10=2+b | | 49=x^ | | 11=15x=-7+13x | | 3(y+8)-5y=16 | | -7y-18=-5(y+6) | | -7y-18=-5(y+6 | | 5x+5=2- | | -84=7v | | x^=81 | | -2x-6x-7=4x | | u-5.89=7.2 | | 4=-4+s | | 4-4u=-20 | | 13+1x=11x+9 | | 3/4=(2/4)x |